Iron-related parameters are altered between C57BL/6N and C57BL/6J mus musculus wild-type substrains: letter - Marques, Oriana; Neves, Joana; Horvat, Natalie; Colucci, Silvia; Guida, Claudia; Muckenthaler, Martina (HemaSphere, 2019)
An abstract is unavailable.
Gesehen am 14.10.2020